Conclusion - Gorman, Sean; Lusher, D.; Reeves, K. (Routledge, 2016)
This conclusion discusses some recent examples of racism in AFL in order to explore the question of ‘how far have we come in the AFL when it comes to racism?’ This paper also discusses what the potential future trajectories are for Rule 35 and the findings from the Australian Research Council Linkage project that this book came from.